Relationship between skeletal malocclusion and dental anomalies in Nepalese population - Pant, Bashu Dev; Rajbhandari, Anjana; Pradhan, Resina; Bajracharya, Manju (Orthodontic Journal of Nepal, 2019)
Introduction: Teeth eruption is important for the development of alveolar process which increases vertical height of the face and third molar is the last tooth to erupt in the oral cavity after birth. The aim of this study was to determine relationship between skeletal malocclusion and dental anomalies in Nepalese population. Materials & Method: A sample of 170 patients with agenesis of at least one third molar was divided into four groups according to the third-molar agenesis pattern. Panoramic radiographs, lateral cephalograph and cast models were used to determine the skeletal malocclusion and associated dental anomalies. The Pearson chi-square test was used for stastical analysis. Result: Among 170 patients more than half of the patients were female with the average age being 18.15 ± 3.64 years. Majority of the patients had Class I skeletal malocclusion followed by Class II and III but on group wise comparison of patients with different skeletal patterns Class I skeletal malocclusion had highest prevalence of dental anomalies followed by Class III and Class II malocclusion. Conclusion: Prevalence of third-molar agenesis was more in skeletal class I malocclusion followed by class II and III but skeletal Class I malocclusions had more dental anomalies followed by class III and class II malocclusion.